Advances in engineering plasticity and its applications : proceedings of the Asia-Pacific Symposium on Advances in Engineering Plasticity and Its Applications, AEPA '96, 21-24 August 1996, Hiroshima, Japan - Abe, T. (Takeji), 1939-; Tsuta, T. (Toshio) (Pergamon, 1996)
AEPA '96 provides a forum for discussion on the state-of-art developments in plasticity. An emphasis is placed on the close interaction of the theories from macroplasticity, mesoplasticity and microplasticity together with their applications in various engineering disciplines such as solid mechanics, metal forming, structural analysis, geo-mechanics and micromechanics. These proceedings include over 140 papers from the conference including case studies showing applications of plasticity in inter-disciplinary or nonconventional areas.